Department of the Sociology of Rural Areas of Nicolaus Copernicus University in Toruń - Zabłocki, Grzegorz (Eastern European Countryside, 2024)
Zakład Socjologii Obszarów Rustykalnych [the Department of the Sociology of Rural Areas] came into existence in 1995 as a part of Institute of Sociology of Nicolaus Copernicus University in Toruń. However, works in the field of the rural sociology were undertaken in Toruń already more than twenty years earlier, in Research Station of the Institute of Rural and Agricultural Development of the Polish Academy of Sciences that exists in this town since 1972 and in the Department of Sociology created in 1976 at Nicolaus Copernicus University. The spectacular achievement of this environment was playing the role of the host of the 4th World Congress of Rural Sociology, organized in 1976, and calling into existence Postgraduate Studies of the Rural Sociology in 1982, existing intermittently up till now. To these activities greatly contributed: Professor Zbigniew Wierzbicki, the worker of the Institute of Philosophy and Sociology Of the Polish Academy of Sciences, who in the eighties had taken up the job at Nicolaus CopernicusUniversity, ProfessorWłod imierz Wincławski, who was then theHead Zakłaem of Socjologii the Department of Sociology, and then (from 1984) the head of the Chair of Sociology, which was transformed into the Institute of Sociology in 1995. This development was connected with the strive of the workers of the Department of Sociology and then the Chair of Sciology for launching MA Sociology studies at Nicolaus Copernicus University, which was achieved in 1989r.